Aethionema arabicum dimorphic seed trait resetting during transition to seedlings - Arshad, Waheed; Steinbrecher, Tina; Wilhelmsson, Per K.I.; Fernandez-Pozo, Noe; Pérez, Marta; Mérai, Zsuzsanna; Rensing, Stefan A.; Chandler, Jake O.; Leubner-Metzger, Gerhard (Frontiers in Plant Science, 2024)
The transition from germinating seeds to emerging seedlings is one of the most vulnerable plant life cycle stages. Heteromorphic diaspores (seed and fruit dispersal units) are an adaptive bet-hedging strategy to cope with spatiotemporally variable environments. While the roles and mechanisms of seedling traits have been studied in monomorphic species, which produce one type of diaspore, very little is known about seedlings in heteromorphic species. Using the dimorphic diaspore model Aethionema arabicum (Brassicaceae), we identified contrasting mechanisms in the germination responses to different temperatures of the mucilaginous seeds (M+ seed morphs), the dispersed indehiscent fruits (IND fruit morphs), and the bare non-mucilaginous M- seeds obtained from IND fruits by pericarp (fruit coat) removal. What follows the completion of germination is the pre-emergence seedling growth phase, which we investigated by comparative growth assays of early seedlings derived from the M+ seeds, bare M- seeds, and IND fruits. The dimorphic seedlings derived from M+ and M- seeds did not differ in their responses to ambient temperature, water potential and salinity. The phenotype of seedlings derived from IND fruits differed in that they had bent hypocotyls and their shoot and root growth was slower, but the biomechanical hypocotyl properties of 15-day old seedlings did not differ between seedlings derived from germinated M+ seeds, M- seeds or IND fruits. Comparison of the transcriptomes of the natural dimorphic diaspores, M+ seeds and IND fruits, identified 2,682 differentially expressed genes (DEGs) during late germination. During the subsequent 3 days of seedling pre-emergence growth the number of DEGs was reduced 10-fold to 277 root DEGs and 16-fold to 164 shoot DEGs. Among the DEGs in early seedlings were hormonal regulators, in particular for auxin, ethylene and gibberellins. Further to this, DEGs were identified for water and ion transporter, nitrate transporter and assimilation enzymes, and cell wall remodelling protein genes encoding enzymes targeting xyloglucan and pectin. We conclude that the transcriptomes of seedlings derived from the dimorphic diaspores, M+ seeds and IND fruits, undergo transcriptional resetting during post-germination pre-emergence growth transition phase from germinated diaspores to growing seedlings.